Spatio-temporal efficiency in a taxi dispatch system - SANTANI, Darshan (Institutional Knowledge at Singapore Management University, 2008)
In this paper, we present an empirical analysis of the GPS-enabled taxi dispatch system used by the world’s second largest land transportation company. We first summarize the collective dynamics of the more than 6,000 taxicabs in this fleet. Next, we propose a simple method for evaluating the efficiency of the system over a given period of time and geographic zone. Our method yields valuable insights into system performance—in particular, revealing significant inefficiencies that should command the attention of the fleet operator. For example, despite the state of the art dispatching system employed by the company, we find imbalances in supply and demand during peak business hours, often resulting in unacceptably high waiting times for passengers. Surprisingly, we also find imbalances during off-peak hours in certain zones. Finally, we discuss how techniques from multi-agent systems research, such as distributed coordination and market-based resource allocation, may be effective in improving the performance of this important mode of public transportation.